2000
DOI: 10.1179/146580100101540761
|View full text |Cite
|
Sign up to set email alerts
|

Fibre reinforced composite–steel connections for transverse ship bulkheads

Abstract: The structural performance of a symmetric steel to composite bonded joint has been examined. Numerical predictions and experimental results on the mechanical strength of the joint are presented. The experimental data and the findings from this study provide useful guidelines to ship designers for using large composite structural components in steel ships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…An alternate method of reducing the stress concentration at the end of the joint is to locally increase the adhesive thickness. Wright et al (2000) found that increasing the thickness of the bond line resulted in a reduction in the stiffness of the adhesive layer, reducing the stress concentration at the ends of the joint and thereby increasing its overall strength. Slight edge preparation of the steel was shown to further reduce the stress concentration.…”
Section: Cfrp Detailingmentioning
confidence: 99%
“…An alternate method of reducing the stress concentration at the end of the joint is to locally increase the adhesive thickness. Wright et al (2000) found that increasing the thickness of the bond line resulted in a reduction in the stiffness of the adhesive layer, reducing the stress concentration at the ends of the joint and thereby increasing its overall strength. Slight edge preparation of the steel was shown to further reduce the stress concentration.…”
Section: Cfrp Detailingmentioning
confidence: 99%
“…The "CIRIA Design Guide" [26] provides detailed design guidance for strengthening metallic structures using externally bonded FRP. Wright et al [27] experimentally investigated a joint between steel plates and FRP laminate and found that, by increasing the thickness of the adhesive layer, the relative stress concentration level was reduced by 21%. Ekiz and El-Tawil [28] carried out an analytical and experimental research program in order to investigate the buckling behavior of the compressive steel braces strengthened with CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Toftegaard and Lystrup (2005) studied the mixed joint between FRP and steel plate by static compression and bending test, which proved that the joint structure had enough static strength. Wright, Wu and Gibson (2000) used the joint structure between FRP and steel plate in hull horizontal bulkhead, carried on tensile, compression and lateral bending test, found that the strength of the symmetric joint structure is better. Clifford, Manger and Clyne (2002) analyzed geometrical characteristics and mechanical properties of the mixed joint between composite material and steel structures, and focused on the embedded steel plate length's influence on the bending strength.…”
Section: Introductionmentioning
confidence: 99%